Analyze the Influence of the Top-Down Approach on the Reading Comprehension - Lase, Herni Trisna; Sri Mawarni Gulo; Elfin Kurnia Telaumbanua; Kristina Gulo; Afore Tahir Harefa (Indonesian Journal of Teaching and Learning, 2024)
The goals of this study was to describe the effect of top-down approach in reading comprehension for students at Nias University. This study used descriptive qualitative design as the research design. The sample of this study was eighteen students of English education study program. The data collection technique used in this study was through a test containing several questions for students. The questions were top-down questions based on the indicators of top-down questions. As for the results of data collection, the researcher obtained several student answer sheets based on the questions given, namely there is a significant effect of using the Top Down approach on students' reading comprehension. This means that students who are treated using the top down approach are better. It is evident that students who have taken the test given are able to understand and do the test given by the researchers